Copper shaft-hole axes and early metallurgy in south-eastern Europe : an integrated approach - Heeb, Julia, (Archaeopress archaeology., 2014)
Although the copper axes with central shaft-hole from south-eastern Europe have a long history of research, they have not been studied on a transnational basis since the 1960s. What has also been missing, is trying to use as many methods as possible to better understand their production, use and context. A database was compiled to find answers to questions regarding patterns of distribution, context, fragmentation and deformation. Aspects of production were considered through experimental archaeology, metallographic analysis and a re-discovered axe blank with missing shaft-hole. The typology was re-evaluated and modified to ensure comparability across modern national boundaries. The integration of these approaches yielded some interesting results.